Evolusi kepimpinan : transformasi bitara Najib Razak, 1976 sehingga 2009 - Khairil Annas Jusoh ([Kuala Lumpur : Kasturi Jingga Corp., 2011)
Political journey of Najib Tun Razak in Malaysian politics from 1976 to 2009.
Transformasi bitara Najib Razak, 1976 sehingga 2009
Includes bibliographical references (p. 129-132).
Keywords: Najib Tun Razak, -- Datuk; Politicians -- Malaysia -- Biography; Prime ministers -- Malaysia -- Biography; Malaysia -- Politics and government